Arterial cannulation site and ventilation strategy modulate cerebral injury in a rat cardiopulmonary bypass model of Harlequin syndrome - Chadi Aludaat; Gabriel Saiydoun; Saade Saade; Jean-Marc Baste; Vincent Magnan; Fabien Doguet; Fabrice Bauer; Jeremy Bellien; Paul Mulder; Emmanuel Besnier (Intensive Care Medicine Experimental, 2026)
Abstract Background Differential hypoxemia, or Harlequin syndrome, is a critical concern during veno-arterial extracorporeal membrane oxygenation (VA-ECMO), especially when femoral artery cannulation delivers retrograde flow. This phenomenon may impair cerebral oxygenation and promote brain injury. We investigated whether the arterial cannulation site and ventilation strategy influence acute cerebral injury in a rat cardiopulmonary bypass (CPB) model. Methods Forty male Wistar rats were randomized into four groups ( n = 10 each) according to the arterial cannulation site (carotid [anterograde, A-CPB] or femoral [retrograde, R-CPB]) and ventilation strategy (normal [NV, 100% tidal volume] or low [LV, 50% tidal volume]). All underwent 60 min of CPB at 50–60 mL/kg/min. Systemic hemodynamics, arterial blood gases, and plasma biomarkers of cerebral injury (neuron-specific enolase [NSE] and S100B) were measured. Postmortem brain water content was quantified to assess edema. Results Mean arterial pressure and heart rate were comparable across groups. Oxygenation (PaO₂) was preserved, whereas PaCO₂ was higher under low ventilation (A-CPB LV vs. A-CPB NV, p = 0.002; R-CPB LV vs. R-CPB NV, p = 0.030). Lactate levels increased significantly in the R-CPB LV group compared with the A-CPB NV group ( p = 0.004). At 60 min, NSE and S100B were markedly elevated in the R-CPB LV group compared with the other groups ( p < 0.001). Regional brain edema was significantly greater in the cerebellum and left telencephalon of R-CPB LV animals ( p < 0.001 and p = 0.002, respectively), whereas other regions showed no significant changes. Conclusions Femoral retrograde perfusion, particularly under reduced ventilation, exacerbates biochemical and structural markers of cerebral injury in a rat CPB model. These findings reproduce key pathophysiological features of Harlequin syndrome and emphasize the importance of proximal cannulation strategies and optimized ventilation to preserve cerebral oxygen delivery during VA-ECMO support.